Atomic, molecular and optical physics section: (LU FMOF Laser Centre section): Book of Abstracts : 31st of January 2023, 10.00 AM, online - 81st International Scientific Conference of the University of Latvia (My University, 2023)
This book of abstracts is made for the Laser Centre section "Atomic, molecular and optical physics section", that occurred as a part of the 81st International Scientific Conference of the University of Latvia. This section was organized by the staff of Laser Centre of the University of Latvia and was held on the 31st of January, 2023. The book of abstracts contains contributions from researchers working on various light-matter interaction problems from all four laboratories of the Laser Center - Atomic and Molecular Physics Laboratory, Molecule Optical Polarization Laboratory, Color centre laboratory and Laboratory of Astrospectroscopy.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics::Atomic and molecular physics::Atomic physics; Research Subject Categories::NATURAL SCIENCES::Physics::Atomic and molecular physics::Molecular physics; Research Subject Categories::NATURAL SCIENCES::Physics::Astronomy and astrophysics::Formation and development of stars